THE EFFECTIVENESS OF INTERACTIVE INTEGRATED SCIENCE E-MODULE WITH CONNECTED TYPE TO IMPROVE STUDENT'S MASTERY ON ENERGY TOPIC - Mas'ud Mas'ud; Teja Pratama Putra; Zulfarina Zulfarina; Roza Linda (International Journal of Educational Best Practices, 2021)
Efforts to improve the quality of Integrated Science learning for junior high schools in the era of globalization that are following the challenges of 21st-century education can be done through the use of connected type interactive e-modules. The study was conducted to determine the effectiveness of the e-module on students' mastery of energy concepts. The research method used is a descriptive quantitative quasi-experimental type with a matching-only pretest-posttest control group design. The research was conducted in one of the public junior high schools in Bangkinang with a purposive sampling technique. Data were collected using research instruments in the form of mastery of concepts in energy material. Data analysis was performed using pre-requisite test, statistical test (different test; t-test), and N-Gain test. The results obtained show that the use of the connected type of integrated science interactive e-module can improve students' mastery of concepts on energy material in the experimental class with the medium category.